National Policies and Older People's Healthcare in Sub-Saharan Africa: A Scoping Review - Sule Saka; Frasia Oosthuizen; Manimbulu Nlooto (Ubiquity Press, 2019)
Background: Sub-Saharan Africa (SSA) is undergoing a rapid demographic change, with more people reaching old age. There is, however, little information available about healthcare policies with regards to this age group in this region of the world. Objectives: This scoping review aims to map the healthcare policies in sub-Saharan Africa (SSA) after the 2002 United Nations Madrid International Plan of Action on Ageing (MIPAA) with an eye towards to identifying strategies for promoting older people's access to health care, integration of older people's diseases into primary health care and the level of training and research in geriatrics and gerontology in SSA. Methods: This review adopted Arskey and O'Malley's five-step methodology for scoping review and used the guide by Levac et al to operationalize the steps. Potentially relevant literature in English published between January 2003 and December 2017 was identified through PubMed, Google Scholar, EBSCOhost, and manual search. Articles that related to ageing in SSA in line with the aims of the review were included. The identified articles were independently assessed by the authors and the decision on the articles to be included was reached by a consensus. Findings: A total of 363 articles were identified through the databases and manual search of which only 4.7% (17/363) of the articles were included in the review. The findings showed that many SSA countries have formulated policies on healthy ageing and a few have policies to promote access to health care for the older people. The integration of non-communicable diseases (NCDs) management into primary health care (PHC) is encouraging but mental health appears to have been completely neglected. Training and research in gerontology and geriatrics are hardly supported by governments in SSA. Conclusions: Significant progress has been made by the SSA countries in policy formulation with regards to older persons but not much has been achieved with the implementation of the policies.